Blogs : a situated learning experience to enhance students' writing skills. (2021)
The present document embodies the design of a proposal of pedagogical and didactic innovation based on situated writing activities and the use of blogs as learning tools within a framework of blended learning. The context in which this proposal seeks to be implemented is a group of eleventh graders at a public school in Bogotá, Colombia. After researching the context of the target population, it was possible to determine that decontextualized lessons and writing activities have triggered students’ lack of interest and struggles when expressing themselves in their compositions. Hence, the objective of this didactic proposal is to foster students’ written expression from a situated perspective. Nine lesson plans were designed to be carried out during 18 sessions of 60 minutes each. They aim at providing the teachers with the instructions and material to lead learners to foster their writing skills in L2 through the use of blogs.